Safety During Ureteroscopy: Radiation, Eyes, and Ergonomics - Miller, David T.; Semins, Michelle J. (Frontiers in Surgery, 2021)
It is known that urologic surgeons are at risk of work-place injury due to the physical requirements of operating and exposure to hazards. These hazards include radiation, exposure to body fluids, use of laser energy, and orthopedic injury due to the physical nature of operating. The risks that these hazards present can be mitigated by implementing several evidence-based safety measures. The methods to protect against radiation exposure include keeping radiation usage in the operating room as low as reasonably achievable, donning lead aprons, and wearing protective glasses. Additionally, protective glasses decrease the risk of eye injury from laser injury and exposure to body fluids. Finally, practicing sound surgical ergonomics is essential to minimize the risk of orthopedic injury and promote career longevity. The interventions discussed herein are simple and easy to implement in one's daily practice of urology.